Efficacy and Safety of Candesartan 16 mg versus 64 mg Candesartan in Renal Disease Patients with Proteinuria: A Systematic Review and Meta-analysis - Gonius, Andry; Adisaputra, Arnaz; Farahdina, Farahdina; Rifdah, Salsabila; Indrasari, Astried; Tjempakasari, Artaria (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Chronic kidney disease (CKD) is a global health burden in the world. One of the complications of CKD is proteinuria. Candesartan is a drug that is often used in CKD patients to improve proteinuria. There are several studies that suggest that using a higher dose of candesartan can further improve its effectiveness in reducing proteinuria in CKD patient AIM: This paper is aimed to review the effectiveness and safety at a supramaximal dose of 64 mg to a dose of 16 mg of candesartan. METHODS: We performed a literature search using PubMed, SCOPUS, EuropePMC, ProQuest, and Cochrane Central Databases using these keywords: “candesartan” and “16 mg” and “64 mg” or “proteinuria renal disease” or “albuminuria” and “blood pressure” that were published within the year of 1980–2021. Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) protocol were used to conduct this meta-analysis. We included randomized controlled trials, prospective cohort, retrospective or clinical observational evaluating the effect of candesartan in 16 mg or 64 mg in proteinuria renal disease patients regardless of clinical status. Non-randomized, controlled trials reporting efficacy were included if these trials were in the scope of our topic. Duplicate studies were excluded. Dichotomous variables were analyzed with the Mantel-Haenszel statistical method using risk ratio as the summary statistic and reported with 95% confidence intervals (CIs). RESULTS: Forty-six studies were initially generated using our search keyword. After applying inclusion and exclusion criteria, we included two studies in our analysis. Our pooled analysis found that candesartan 16mg dosage administration, compared to 64mg, was not associated with proteinuria reduction (std mean diff: −10.92 [95% CI: −40.09–18.26], p = 0.46). CONCLUSION: Candesartan supramaximal dosage 64 mg did not differ significantly in proteinuria reduction and blood pressure reduction against candesartan 16 mg. More studies are needed to determine this efficacy and safety.